Effect of gabapentin pretreatment on myoclonus after etomidate: a randomized, double-blind, placebo-controlled study - Cakirgoz, Mensure Yilmaz; Demirel, Ismail; Duran, Esra; Ozer, Ayse Belin; Hanci, Volkan; Turkmen, Ulku Aygen; Buyukyildirim, Aslihan (Elsevier Science Inc, 2016)
Aim: To evaluate the effects of three different doses of gabapentin pretreatment on the incidence and severity of myoclonic movements linked to etomidate injection. Method: One hundered patients, between 18 and 60 years of age and risk category American Society of Anesthesiologists I-II, with planned elective surgery under general anesthetic were included in the study. The patients were randomly divided into four groups and 2 h before the operation were given oral capsules of placebo (Group P, n = 25), 400 mg gabapentin (Group G400, n = 25), 800 mg gabapentin (Group G800, n = 25) or 1200 mg gabapentin (Group G1200, n = 25). Side effects before the operation were recorded. After preoxygenation for anesthesia induction 0.3 mg kg(-1) etomidate was administered for 10 s. A single anesthetist with no knowledge of the study medication evaluated sedation and myoclonic movements on a scale between 0 and 3. Two minutes after induction, 2 mu g kg(-1) fentanyl and 0.8 mg kg(-1) rocuronium were administered for tracheal intubation. Results: Demographic data were similar. Incidence and severity of myoclonus in Group G1200 and Group G800 were significantly lower than in Group P; sedation incidence and level were appreciably higher compared to Group P and Group G400. While there was no difference in the incidence of myoclonus between Group P and Group G400, the severity of myoclonus in Group G400 was lower than in the placebo group. In the two-hour period before induction other than sedation none of the side effects related to gabapentin were observed in any patient. Conclusion: Pretreatment with 800 mg and 1200 mg gabapentin 2 h before the operation increased the level of sedation and reduced the incidence and severity of myoclonic movements due to etomidate. (C) 2015 Sociedade Brasileira de Anestesiologia. Published by Elsevier Editora Ltda.
Efeito do pré-tratamento com gabapentina sobre a mioclonia após etomidato: Um estudo randômico, duplo-cego e controlado por placebo
Keywords: Etomidate; Injection pain; Myoclonus; Gabapentin